Sosialisasi Digital Parenting: Upaya Pengentasan Risiko Digital dan Penguatan Literasi Digital Anak dan Keluarga - Rahman, Maulida Aulia; Gunawan, Dani; Adiredja, Rajji Koswara; Ramdan, Mohammad; Putra, Karantiano S; Sidiq, Purnomo (IPI Press, 2025)
In the increasingly advanced digital age, technology has become an integral part of human life. Children of the ‘digital natives’ generation have a natural ability to use digital devices such as smartphones, tablets and computers from an early age. However, this exposure brings not only benefits, but also significant digital risks. These risks include exposure to negative content, cyberbullying, technology addiction and privacy violations. Therefore, digital parenting emerges as a strategic approach that needs to be socialised to parents to guide children in using technology safely, responsibly and productively. Digital parenting is a responsibility that not only involves supervision, but also includes education on digital literacy and ethical use of technology. This approach demands collaboration between parents, educators and the community to ensure children get the most out of technology while being protected from threats. This article will discuss the contents of digital parenting counselling including the urgency, objectives, strategies, benefits, and challenges in implementing digital parenting.